Peran Institusi Lokal Dalam Pengembangan Kegiatan Pariwisata Desa Giritengah Kabupaten Magelang - Eri Rajasa Pratama; Holi Bina Wijaya (Jurusan Perencanaan Wilayah dan Kota, 2018)
Community-based tourism is one of the substantial concept needed in terms of enhancing tourism activities. Situated in the countryside of Giritengah, Borobudur, Magelang, this is one prospective area for tourism development with the likes of Punthuk Mongkrong, Punthuk Sukmojoyo, Bukit Gupakan, Local Honeybee Farm, and Local Art Community “Saking Ndene.” Creative traits of its people and independent movement towards tourism development have become another interesting point as the local citizens contributed in initiating local institutions’ establishments. These groups exist under the direct supervisory of higher authorities called Balkondes which responsible as promotor and supervisor of all tourism aspects.This study aims to determine how significant the role of local institutions in Giritengah’s tourism development activities. Mix methods approach will be used with the follow-up data obtained through questionnaires, observation, and direct interviews with community groups and village councils. Quantitative & qualitative descriptive techniques will be applied to expose all four-main analysis. From that aforementioned analysis, conclusions have been made as it discovered the existence of local institutions role in tourism development showed the mutual partnership between stakeholders. Partnership forms adhere to the tourism activities operational and supervisory that bring direct impact in escalating new business initiatives, various job opportunities, and alternative tourism options to attract more visitors.